Selection of Appropriate Methods Analysis of Cytotoxicity Assay for In Vitro Study: Selection of Cytotoxicity Assay for In Vitro - Mukem, Sirirak; Maungchanburi, Saowanee (PSU Medical Journal, 2023)
Cell viability is defined as the number of living cells and the proliferation of cells. It is a vital indicator for understanding mechanisms of action and cytotoxicity that involve cell survival or cell death following exposure to agents, including crude extract, pure compounds and drugs. A broad spectrum of cytotoxicity assay is currently used to estimate toxicology and pharmacology. In fact, methods used to determine viability are typical for the detection of cell growth and cell proliferation. Therefore, cytotoxicity assays are essentially utilized for agent screening to detect whether the test molecules affect cell proliferation or directly display cytotoxic effects. Accumulating evidence demonstrated that regardless of the cell-based assay being used, it is crucial to know how many viable cells remain at the end of the experiment. There are various assay methods based on various functions, such as evaluating structural cell damage (non-invasive and invasive) by cell counting assay, measuring cellular metabolism activity, and determining deoxyribonucleic acid and adenosine triphosphate contents. However, there is no conclusion on whether any method is most accurate and appropriate. Since every research has differentiations and limitations, choosing the proper viability assay, the cell type, the constituent molecule of the substance, concentration and even the extraction method should be considered. This particular review aims to provide information on different cytotoxicity assays together with their own advantages and disadvantages. Additionally, it may be possible to select the appropriate agent concentration, have no false-positive results, and increase the reproducibility of their research design.